Argon in β Pictoris–Entrapment and Release of Volatile in Disks - Yanqin Wu; Kadin Worthen; Alexis Brandeker; Christine Chen (The Astrophysical Journal)
Chemical compositions of planets reveal much about their formation environments. Such information is well sought-after in studies of solar system bodies and extrasolar ones. Here, we investigate the composition of planetesimals in the β Pictoris debris disk by way of its secondary gas disk. We are stimulated by the recent JWST detection of an Ar  ii emission line and aim to reproduce extensive measurements from the past four decades. Our photoionization model reveals that the gas has to be heavily enriched in C, N, O, and Ar (but not S and P), by a uniform factor of about 100 relative to other metals. Such an abundance pattern is both reminiscent of, and different from, that of Jupiter's atmosphere. The fact that Ar, the most volatile and therefore the hardest to capture into solids, is equally enriched as C, N, and O suggests that the planetesimals were formed in a very cold region ( T ≤ 20–35 K), possibly with the help of entrapment if water ice is overabundant. In the debris disk phase, these volatiles are preferentially outgassed from the dust grains, likely via photodesorption. The debris grains must be “dirty” aggregates of icy and refractory clusters. Lastly, the observed strength of the Ar  ii line can only be explained if the star β Pic (a young A6V star) has sizable chromospheric and coronal emissions, on par with those from the modern Sun. In summary, observations of the β Pic gas disk rewind the clock to reveal the formation environment of planetesimals.